EFEKTIVITAS STRATEGI EVENT MARKETING UNTUK KEBERLANJUTAN BISNIS E-COMMERCE - Logi Mulawarman; Lalu Jatmiko Jati; Ridha Nurul Hayati (Jurnal Pijar, 2023)
Business sustainability is crucial to implement in order to maintain a company's good reputation in the society. A business can maintain its existence by maximizing marketing strategies. Event marketing is a form of marketing that can be implemented by a business, but in practice there are still many businesses or companies that do not understand how event marketing activities work. The purpose of this study is to explain the effectiveness of event marketing strategies in creating a sustainable E-Commerce business. The case study was conducted at E-Commerce X marketing event which was held in October 2022. There were five respondents who were involved in the interview technique. The results show that an event marketing strategy that is carried out offline is more effective in attracting customers and increasing E-Commerce X opportunities to create a sustainable business so that it can exist in the public. Event marketing activities that can create a sustainable business should involve economic, environmental and social approaches.